Correlation between the use of 5-HT agonist drug and aerobic physical exhaustion - Cuquetto, Douglas Colombi (2012)
Introduction: Works of different authors has been shown that, an increase in the concentration of serotonin (5-HT) in the brain during intense and long-term physical exercise, is directly related with a harm in the function of the Central Nervous System (CNS), with corresponding development of the fatigue and consequence decrease of the performance. Materials and methods: Ten rats Wistar was submitted the run-sessions until the exhaustion in treadmill. The experimental protocol consisted in the evaluation of the range run-time of the animals until the exhaustion, divides in three weekly sessions in alternates days. The animals were treated, during seven days, with agonist drug 5-HT, fluoxetine, (10mg/kg/day) dissolved in physiologic solution (NaCl 0,9%) injected intraperitoneally (i.p.). Results: It was observed that the average run time of the animals to exhaustion increased significantly. Conclusion: The present study suggest that the chronicle administration (12 days) of fluoxetine in the dose of 10 mg/kg/day (i.p.) increase substantially the run-time until the exhaustion in rats submitted the exercises in treadmill.